The Role of Social Media in Product Promotion Efforts Reviewed from an Islamic Economic Perspective - Sholih, Muhammad Nur; Ashar, Indana Almas (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the role of social media in product promotion strategies from an Islamic economic perspective. In the digital era, social media platforms such as TikTok, Instagram, and Facebook have become essential tools for PT Deles in promoting their products. By leveraging creative content, appealing visuals, and direct interaction with consumers, PT Deles successfully increased sales and expanded brand awareness. Social media also enables the company to build brand identity and establish closer relationships with customers through special offers and discounts. This research employs a qualitative method, with data collection techniques including interviews and observations. The findings show that effectively utilizing social media can strengthen Islamic promotional strategies that prioritize ethical values, transparency, and honesty. Thus, promotional strategies based on Islamic principles can be optimally integrated into digital platforms to achieve positive outcomes.